Estudo do modo coletivo massivo do líquido de Fermi ferromagnético - Brentan, Henrique Brito (Universidade Federal de São Carlos, 2014)
The present dissertation is divided in 4 chapters. From chapter 1 to 2, we review some basic concepts of the normal Fermi liquid theory (a set of interacting fermions in correspondence with the Fermi gas) such as quasiparticles, some equilibrium properties, and we also derive the kinetic equation for spin waves in presence and in absence of an external magnetic field. The main purpose of this work is the study of the massive mode (which has a gap in the energy spectrum, ω(q=0)≠0) that exists in the liquid s isotropic ferromagnetic phase. The idea of chapter 3 is to review how the interaction between fermions leads to phase transitions in Landau Fermi liquid theory and also the concepts of broken symmetry and order parameter. Chapter 4 can be divided in three parts. In the first, we present the basis for ferromagnetic Fermi liquid theory (FFLT) and discuss how the phase transition from normal to ferromagnetic is accompanied by spontaneously broken symmetry, leading to propagating modes described by elementary excitations such as the Nambu-Goldstone mode and the massive mode. A second part, a review is taken in order to discuss the massive mode from "birth" to characterization as a massive mode like the Anderson-Higgs mode. Lastly, the third part presents the results obtained for the behavior of the massive mode in the presence of an external magnetic field. We compare the results obtained for the dynamic structure form factor with the ones obtained in previous works.
Keywords: Física; Matéria condensada; Modo massivo; Líquidos quânticos; CIENCIAS EXATAS E DA TERRA::FISICA